2002
DOI: 10.1074/jbc.m111013200
|View full text |Cite
|
Sign up to set email alerts
|

Both N- and C-terminal Domains of Parathyroid Hormone-related Protein Increase Interleukin-6 by Nuclear Factor-κB Activation in Osteoblastic Cells

Abstract: Parathyroid hormone (PTH)-related protein (PTHrP) seems to affect bone resorption by interaction with bone cytokines, among them interleukin-6 (IL-6). Recent studies suggest that nuclear factor (NF)-B activation has an important role in bone resorption. We assessed whether the N-terminal fragment of PTHrP, and its C-terminal region, unrelated to PTH, can activate NF-B, and its relationship with IL-6 gene induction in different rat and human osteoblastic cell preparations. Here we present molecular data demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 57 publications
2
27
0
Order By: Relevance
“…Several studies have shown that NF-B plays an important role in mediating the suppression of P450 expression by inflammatory agents, such as inflammatory cytokines and LPS (40,41). Moreover, it has been reported that PTH and PTH-rP cause dosage-and time-related increases in NF-B in human and rat osteoblastic cells (42,43). Our results support the hypothesis that PTH may act via NF-B to downregulate P450.…”
Section: Figure 5 Effect Of Pth 10supporting
confidence: 88%
“…Several studies have shown that NF-B plays an important role in mediating the suppression of P450 expression by inflammatory agents, such as inflammatory cytokines and LPS (40,41). Moreover, it has been reported that PTH and PTH-rP cause dosage-and time-related increases in NF-B in human and rat osteoblastic cells (42,43). Our results support the hypothesis that PTH may act via NF-B to downregulate P450.…”
Section: Figure 5 Effect Of Pth 10supporting
confidence: 88%
“…In the present study, we demonstrated that NF-κB is a key transcriptional factor in the downregulation of CYPs caused by uremic serum since NF-κB inhibition nearly eliminated the effect of pre-HD serum on CYP expression. These results implicate potential uremic mediators such as PTH and cytokines since these proteins act via NF-κB signaling pathways (13,16). Interestingly, changes in the metabolic clearance of CYP substrates that cannot be explained by transcriptional or translational modifications have also been reported.…”
Section: Discussionmentioning
confidence: 72%
“…MDA-MB-231 cells were also assayed for NF-nB-mediated PTHrP mRNA expression. PTHrP is a causal factor in tumor-mediated osteolysis whose fragments activate NF-nB signaling in osteoblasts (35,36). Real-time RT-PCR did not show a statistically significant difference in PTHrP mRNA expression between wild-type MDA-MB-231 and MDA.mInB cells (data not shown).…”
Section: Resultsmentioning
confidence: 90%
“…Augmented PTHrP expression can increase bone resorption by stimulating osteoblast RANKL mRNA expression, which in turn fosters bone-resorbing activity by the increased number of osteoclasts made available by IL-6 (43). PTHrP fragments also activate NF-nB transcription in osteoblasts, leading to IL-6 gene induction and suggestive of an autocrine/ paracrine role for PTHrP in NF-nB-mediated osteolytic tumor burden (36,44).…”
Section: Discussionmentioning
confidence: 99%